The Emergence of Biosimilars in Indonesia: Guidelines, Challenges, and Prospects - Wardiana, Andri; Ningrum, Ratih Asmana (Annales Bogorienses, 2025)
According to the Food and Drug Administration (FDA), biosimilar is defined as a product which is highly similar to the reference product without clinically meaningful differences in safety, purity and potency. Indonesia is a developing country which has more than 250 million people. In 2008, the world market of biosimilar was USD 100 billions with 10-20% of domestic need from total market. Even though the need is very high, Indonesia still has not been able to produce Biosimilar independently. To stimulate the domestic production on biosimilar, National Agency for Drug and Food Control (NADFC) Republic of Indonesia has assigned Regulation of Biosimilar as Peraturan Kepala Badan Pengawas Obat Dan Makanan Republik Indonesia Nomor 17 Tahun 2015 Tentang Pedoman Penilaian Produk Biosimilar. The guidance covers the quality requirement and evaluation of Biosimilar products. Indonesian Ministry of Health has a strategic plan in biopharmaceutical covering biosimilar, which is going to be developed from 2015 to 2025. The strategy is expected to initiate biosimilar production in Indonesia. This review focuses on the guidelines of biosimilars in Indonesia compared to other international regulatory bodies, as well as the challenges and prospects of biosimilars development.